When Salt Meddles Between Plant, Soil, and Microorganisms - Otlewska, Anna; Migliore, Melania; Dybka-Stępień, Katarzyna; Manfredini, Andrea; Struszczyk-Świta, Katarzyna; Napoli, Rosario; Białkowska, Aneta; Canfora, Loredana; Pinzari, Flavia (Frontiers in Plant Science, 2020)
In extreme environments, the relationships between species are often exclusive and based on complex mechanisms. This review aims to give an overview of the microbial ecology of saline soils, but in particular of what is known about the interaction between plants and their soil microbiome, and the mechanisms linked to higher resistance of some plants to harsh saline soil conditions. Agricultural soils affected by salinity is a matter of concern in many countries. Soil salinisation is caused by readily soluble salts containing anions like chloride, sulphate and nitrate, as well as sodium and potassium cations. Salinity harms plants because it affects their photosynthesis, respiration, distribution of assimilates and causes wilting, drying and death of entire organs. Despite these life-unfavourable conditions, saline soils are unique ecological niches inhabited by extremophilic microorganisms that have specific adaptation strategies. Important traits related to the resistance to salinity are also associated with the rhizosphere-microbiota and the endophytic compartments of plants. For some years now, there have been studies dedicated to the isolation and characterisation of species of plants' endophytes living in extreme environments. The metabolic and biotechnological potential of some of these microorganisms is promising. However, the selection of microorganisms capable of living in association with host plants and promoting their survival under stressful conditions is only just beginning. Understanding the mechanisms of these processes and the specificity of such interactions will allow us to focus our efforts on species that can potentially be used as beneficial bioinoculants for crops